Interest rate impacts on investment: Evidence from Bangladesh: Interest rate impacts on Bangladesh investment (IIUC Business Review, 2026)
Beginning in the early 1990s, Bangladesh implemented the Financial Sector Reform Programs (FSRPs), offering greater earnings on funds and effectively allocating loans in the financial sector by switching from a managed to a market-oriented interest rate system, which was one of the main goals of this extensive scheme. This would encourage expenditures on investment and support the growth of the economy. The main objective of this research is to examine how Bangladesh's interest rate affects the amount of investment made there. The ARDL approach was employed to assess the analysis for the period 1986-2023. The results reveal that the real interest rate has a more pronounced negative impact on investment, with a coefficient of -0.4882 and a p-value of 0.0002, indicating a statistically significant effect. The findings provide important insights for evaluating the outcomes of the Financial Sector Reform Programs (FSRPs) and informing the formulation of future policy strategies. The results are especially valuable for both domestic policymakers and international partners in shaping effective strategies for long-term economic development.IIUC Business Review, Vol.-13, Issue-1, December 2024, pp. 101-116